Determination of the Hypoglycaemic Effect of the Ethanol Stem Bark Extract of Vitellaria paradoxa on Hyperglycemic Wistar Rats - Ekpo, Fidelis Okii; Mamman, Emmanuel; Yakubu, Ojochenemi Ejeh; Danjuma, Janya (African Journal of Biochemistry and Molecular Biology Research, 2024)
This study investigates the hypoglycaemic effects of the ethanol stembark extract of Vitellaria paradoxa on hyperglycemic rats. It also investigates the phytochemical content of ethanol stem bark extract of Vitellaria paradoxa using the method of Soforh. The result shows that the ethano| stem/bark of the plant contains Tannins 3.92/mg/100g, Alkaloid 7.12/mg/100g, Flavonoids 1.03/gm/100g, phenolics 12.72/mg/100g, Glycosides 4.13/gm/100g, saponins 2.15/mg/100g respectively. The hypoglycemic properties of ethanol stem bark extract of Vitellaria paradoxa were investigated using Fifteen albino Wister rats weighing between 200g to 230g were induced with alloxan monohydrate to make them diabetic. The rats were divided into five groups of three rats. The first group were not induced, tagged normal. The second groups were induced sstandard drug glibenclamide throughout the study period. The fourth groups were induced and treated with 250/mg/kg body weight of the ethanol stem/bar extract of Vitellaria paradoxa throughout the study period. The fifth groups were induced and treated with 500/mg/kg body weight of the extract. The fasting blood glucose level of the rats were taken every three days’ interval for 21 days. At the end of 21 days, the rats treated with 250/mg/kg body weight which started with elevated blood glucose level after induction of 207/mg/dl reduces to 124/mg/dl, similarly the treated with 500/mg/kg body weight of the extract with initial elevated blood glucose level after the induction with diabetic of 221/mg/dl got reduced to 145/me/dl. This indicates that ethanol bark tract of Vitellaria paradoxa showed hypoglycemic properties.